ApoA-I/HDL-C levels are inversely associated with abdominal aortic aneurysm progression - Burillo, Elena; Lindholt, Jes S.; Molina-Sánchez, Pedro; Jorge, Inmaculada; Martinez-Pinna, Roxana; Blanco-Colio, Luis Miguel; Tarin, Carlos; Torres-Fonseca, Monica Maria; Esteban, Margarita; Laustsen, Jesper; Ramos-Mozo, Priscila; Calvo, Enrique; Lopez, Juan Antonio; Ceniga, Melina Vega de; Michel, Jean-Baptiste; Egido, Jesus; Andrés, Vicente; Vazquéz, Jesús; Meilhac, Olivier; Martin-Ventura, Jose Luis (Thrombosis and Haemostasis, 2015)
Abdominal aortic aneurysm (AAA) evolution is unpredictable, and there is no therapy except surgery for patients with an aortic size > 5 cm (large AAA). We aimed to identify new potential biomarkers that could facilitate prognosis and treatment of patients with AAA. A differential quantitative proteomic analysis of plasma proteins was performed in AAA patients at different stages of evolution [small AAA (aortic size=35cm) vs large AAA] using iTRAQ labelling, highthroughput nano-LC-MS/MS and a novel multi-layered statistical model. Among the proteins identified, ApoA-I was decreased in patients with large AAA compared to those with small AAA. These results were validated by ELISA on plasma samples from small (n=90) and large AAA (n=26) patients (150 ± 3 vs 133 ± 5 mg/dl, respectively, p< 0.001). ApoA-I levels strongly correlated with HDL-Cholesterol (HDL-C) concentration (r=0.9, p< 0.001) and showed a negative correlation with aortic size (r=-0.4, p< 0.01) and thrombus volume (r=-0.3, p< 0.01), which remained significant after adjusting for traditional risk factors. In a prospective study, HDL-C independently predicted aneurysmal growth rate in multiple linear regression analysis (n=122, p=0.008) and was inversely associated with need for surgical repair (Adjusted hazard ratio: 0.18, 95 % confidence interval: 0.040.74, p=0.018). In a nation-wide Danish registry, we found lower mean HDL-C concentration in large AAA patients (n=6,560) compared with patients with aorto-iliac occlusive disease (n=23,496) (0.89 ± 2.99 vs 1.59 ± 5.74 mmol/l, p< 0.001). Finally, reduced mean aortic AAA diameter was observed in AngII-infused mice treated with ApoA-I mimetic peptide compared with saline-injected controls. In conclusion, ApoAI/ HDL-C systemic levels are negatively associated with AAA evolution. Therapies targeting HDL functionality could halt AAA formation.
Keywords: Vascular remodelling; lipoproteins; proteomics; abdominal aortic aneurysm